Association between cardiovascular anomalies and karyotypes in Turner syndrome patients in Taiwan: A local cohort study - Yu-Yu Chou; Chao-Jan Wang; Chia-Hung Lin; Hung-Tao Chung; Fu-Sung Lo (Pediatrics and Neonatology)
Background: Turner syndrome (TS) is characterized by growth failure, primary ovarian failure, cardiac anomalies, and other anomalies. Cardiovascular abnormalities such as bicuspid aortic valve (BAV), coarctation of the aorta (CoA), aortic stenosis (AS), and aortic dilatation (AD) account for some cases of TS-related early mortality. In this study, we investigated the correlations between cardiovascular phenotypes and karyotypes in TS. Methods: We conducted a retrospective cohort analysis of 105 local patients with TS aged 6–43 years between January 1994 and December 2018. They were categorized into two groups of complete monosomy X (45,X) and other X chromosome abnormalities. Most of the patients underwent echocardiography (n = 88, 83.8%), cardiac computed tomography (CT) angiography, and/or cardiovascular magnetic resonance imaging (MRI) (n = 58, 55.2%). We used independent the Student's t test, chi-square test or Fisher's exact test, and log-rank test to compare differences in continuous data, proportions, and Kaplan–Meier survival analysis results between the two TS groups. Results: 45,X was the most common karyotype (n = 47, 44.8%). Phenotypically, cardiovascular malformations were found in 29 patients with TS (27.6%). BAV (n = 6), CoA (n = 3), AS (n = 2), ASD (n = 1, 2.5%), and PAPVR (n = 1, 2.5%) were found in only the 45,X group. The mean age at AD onset was 25.55 ± 5.78 years (mean ± SD). Survival analysis of age at onset of AD demonstrated no significant difference between the two groups (p = 0.051). Conclusion: Cardiovascular abnormalities, such as BAV, CoA, AS, and AD, are common and potentially progressive in patients with TS, especially those with the 45,X karyotype. They should receive immediate cardiological assessments upon receiving diagnosis, regular assessments, and treatment to carefully control blood pressure, even with no apparent congenital heart disease. Key Words: aortic dilatation, aortic stenosis, bicuspid aortic valve, coarctation of the aorta, turner syndrome